Stem Cell-Based Therapy and Cell-Free Therapy as an Alternative Approach for Cardiac Regeneration - Iwona Deszcz (Stem Cells International)
The World Health Organization reports that cardiovascular diseases (CVDs) represent 32% of all global deaths. The ineffectiveness of conventional therapies in CVDs encourages the development of novel, minimally invasive therapeutic strategies for the healing and regeneration of damaged tissue. The self-renewal capacity, multilineage differentiation, lack of immunogenicity, and immunosuppressive properties of mesenchymal stem cells (MSCs) make them a promising option for CVDs. However, growing evidence suggests that myocardial regeneration occurs through paracrine factors and extracellular vesicle (EV) secretion, rather than through differentiation into cardiomyocytes. Research shows that stem cells secrete or surface-shed into their culture media various cytokines, chemokines, growth factors, anti-inflammatory factors, and EVs, which constitute an MSC-conditioned medium (MSC-CM) or the secretome. The use of MSC-CM enhances cardiac repair through resident heart cell differentiation, proliferation, scar mass reduction, a decrease in infarct wall thickness, and cardiac function improvement comparable to MSCs without their side effects. This review highlights the limitations and benefits of therapies based on stem cells and their secretome as an innovative treatment of CVDs.